2021
DOI: 10.3390/ijerph18116068
|View full text |Cite
|
Sign up to set email alerts
|

Time-Variant Positive Air Pressure in Drainage Stacks as a Pathogen Transmission Pathway of COVID-19

Abstract: Time-variant positive air pressure in a drainage stack poses a risk of pathogenic virus transmission into a habitable space, however, the excessive risk and its significance have not yet been sufficiently addressed for drainage system designs. This study proposes a novel measure for the probable pathogenic virus transmission risk of a high-rise drainage stack with the occurrence of positive air pressure. The proposed approach is based on time-variant positive air pressures measured in a 38 m high drainage stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In response to such a hypothesis, experimental investigations using pilot sewer stacks [ 44 , 47 ], tracer gases studies in buildings [ 35 , 36 , 48 , 49 ] and mathematical simulation [ 50 , 51 ] were conducted to delineate how the vertical outbreak occurred. Figure 1 provided a summary of the vertical outbreak mechanisms showing the possible route of virus-laden airflow, and the pressure profiles of non-flushing periods and flushing periods, respectively.…”
Section: How Did It Happen?mentioning
confidence: 99%
See 2 more Smart Citations
“…In response to such a hypothesis, experimental investigations using pilot sewer stacks [ 44 , 47 ], tracer gases studies in buildings [ 35 , 36 , 48 , 49 ] and mathematical simulation [ 50 , 51 ] were conducted to delineate how the vertical outbreak occurred. Figure 1 provided a summary of the vertical outbreak mechanisms showing the possible route of virus-laden airflow, and the pressure profiles of non-flushing periods and flushing periods, respectively.…”
Section: How Did It Happen?mentioning
confidence: 99%
“…Air may also move down the stack if subjected to entrainment by the falling wastewater as in Fig. 1 B [ 50 , 52 ]. Most of the time (non-flushing periods), the aerosolized pathogens travel from horizontal collection drains, through wastewater pipes or the vent stack, toward the cowl on rooftops under natural buoyancy forces ( Fig.…”
Section: How Did It Happen?mentioning
confidence: 99%
See 1 more Smart Citation
“…Six publications in this review confirmed that viral aerosols in Amoy Gardens' building plumbing were sucked into unit bathrooms through floor drains, contributing significantly to the outbreak, with case studies [ 110 , 113 ], experimental studies [ 107 ], and simulations [ 108 , 111 , 112 ]. Unsurprisingly, another study cluster emerged during the Covid-19 pandemic, employing similar research approaches, such as case studies [ 117 ], experiments [ 115 , 116 ], and modelling [ 109 , 114 , 118 ]. However, the settings of SARS drainage studies were all high-rise Multi-Unit Residential Buildings (MURB), while Covid-19 studies extended the research on hospitals and general high-rise buildings.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses are capable of surviving in sewerage systems for days to weeks [5], and more recently, the SARS Cov-2 pathogen ('COVID-19') has been found in high concentrations in a WC in a hospital building [6]. There is thus strong anecdotal evidence that the spread of COVID-19 is linked to malfunctioning WDSs; this has recently prompted risk assessments Buildings 2021, 11, 344 2 of 18 to have been carried out high-rise buildings [7,8]. These assessments indicate that risk is most substantial in the upper floors of high-rise buildings, and is non-negligible.…”
Section: Introductionmentioning
confidence: 99%